Arsenic fractionation in estuarine sediments: Does coastal eutrophication influence As behavior?. Issue 1 (15th July 2015) - Sá, Fabian; Sanders, Christian J.; Patchineelam, Sambasiva Rao; Machado, Eunice da Costa; Lombardi, Ana Teresa
Highlights: Arsenic fractionation are studied in sediment profiles of distinct trophic areas. As behavior in estuaries are related to trophic states and marine vegetation. Reactive As and pyrite increases with depth in impacted coastal soils. Abstract: The Paranaguá Estuarine Complex (PEC) includes the naturally oligotrophic (NO) Mel Island which is surrounded by sea grasses, a naturally eutrophic (NE) Benito Inlet adjacent to mangrove wetlands and the highly impacted eutrophic (IE) Paranaguá Bay, home of one of Brazil's largest ports. The results from this study indicate that reactive As and pyrite increase with sediment depth near Paranaguá port in the IE region. At the NE region, near a mangrove fringe, the reactive As, Fe, Mn and pyrite remained relatively high along the sediment column while near the sea grasses at NO the As contents were low. The degree of trace metal pyritization (DTMP) and the degree of pyritization (DOP) was highest at the IE site, slightly increasing with depth. These baseline results indicate that influence of trophic conditions and presence of marine vegetation may be directly related to As behavior in coastal systems.